A new species of the genus Ctenophora Meigen (Diptera: Tipuloidea: Tipulidae) from China, with a key to the world species - Men, Qiu-Lei; Huang, Min-Yi (Zootaxa, 2014)
One new species of the genus Ctenophora Meigen, 1803, C. fumosa Men, sp. nov. (southern China: Anhui) is described and illustrated. A key to known species along with a checklist of known species of the genus Ctenophora are provided. The type specimens of the new species are deposited in the animal specimen room, School of Life Science, Anqing Normal University, Anqing, Anhui Province, China.